Hubungan Antara Status Pemberian Asi Dengan Perkembangan Motorik Halus Pada Bayi Usia 7 - 12 Bulan Di Desa Tohudan Kecamatan Colomadu Kabupaten Karanganyar - RISMANTI, Depa; , Dyah Widowati, SKM; , Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
Background : Breast milk is the main meal at the beginning of the birth of the baby. Exclusive breastfeeding is given at least until the age of 6 months without any given complementary feeding. Breast milk is very important for the growth and development of infants. Substances contained in breast milk is LPUAs (Long Chain Polyunsatured Fatty Acid) very useful for vision and psychomotor development of infant especially fine motor baby. Fine motor is a skill that requires the ability to control the small muscles/refined to achieve a successful implementation skill. Purpose : Determine the relationship between the status of breasfeeding with fine motor development in infants aged 7 - 12 months. Method of the Research : This study is an observational study with cross sectional approach. Number of research subjects as much as 40 respondent were selected based on total sampling method. Data identity of the parents and the baby is obtained by using a questionnaire, fine motor outcome data obtained by measuring and assessing the fine motor using KPSP (Pre Screening Questionniare Development) aged 7 - 12 months. Data analysis using Chi Square correlation test. Result : Status of breastfeeding research shows that 60 percent of the study had no exclusive breastfeeding status, while fine motor development of infants in this study showed 42,5 percent according to the p value < 0,05 is 0,000. Conclusion : There was a significant relationship between the status of breastfeeding with fine motor in infants aged 7 - 12 bulan months in the village Tohudan subdistrict district Colomadu Karanganyar